Social Innovation in Rural Regions: Older Adults and Creative Community Development - Anika Noack; Tobias Federwisch (Rural Sociology, 2020)
Many so-called structurally disadvantaged rural regions are characterized by an ongoing demographic change, low economic productivity, and an insufficient infrastructure. Paradoxically, citizens of such regions are often urged to address local challenges by developing innovative ideas, products, or services. Innovation is becoming a “message of salvation” and imperative to local action due to a rise of an innovation regime that conceptualizes innovation as reflexive and ubiquitous. Unlike cities, however, disadvantaged rural regions are often seen as not conducive to innovation. And older adults are rarely ever regarded as potential innovators. This article will examine how innovations emerge in disadvantaged rural regions and what role older adults play in this context. It focuses on social innovation which is important for processes of rural renewal. Drawing on insights gained through the “Innovation in Rural Municipalities” research project, the paper illustrates the resourcefulness of older adults in the context of socially innovative community development. Older adults can in fact act as drivers of innovative projects, actively participate in and make use of social innovations. Their specific role, however, depends on their personal motives, community-related interests, and available resources.
Keywords: 710